مفهوم الألوهية لدى الديانة اليهودية والنصرانية (دراسة نقدية). (Journal of the College of Basic Education, 2025)
The issue of divinity is an important human issue, concerning all of humanity throughout history, and this issue will remain fundamental and central to human and cosmic existence, as it has sparked a large and long historical controversy regarding the truth of God, and the extent of his relationship with the universe and man, so its concept has oscillated between one god who has died, and another. Incarnated in human form, and others mythical and superstitious, as well as spiritual or natural, and in all cases, minds have become lost and confused in their interpretation of the truth of God, and clarifying His essence, in addition to the many philosophical statements that have tried to reach His knowledge, but they have only come up with philosophical reflections that have nothing to do with the facts. Or it can be described as illusory, meaning the divine mixed with the human, until the concept of divinity stabilized to some extent with the advent of heavenly religions calling for absolute oneness, noting that some of them still retained some customs and pagans resulting from ancient beliefs. Accordingly, this research seeks to clarify the concept of divinity in the Jewish and Christian religions, and to highlight the points of similarity and difference between them, following the descriptive and analytical approach.